Comparison Of Subjective Refraction Under Cycloplegia Versus Post Mydriatic Refraction In Pediatric Population: Subjective Refraction under Cycloplegia Versus Post Mydriatic Refraction - Tahir, Ammara; Bibi, Irfana; Akhtar , Faiza; Jabeen, Tahira; Arslan Ashraf, Muhammad; Yousaf, Sobia; Anwar Faridi, Tallat (Pakistan BioMedical Journal, 2022)
Reduced vision throughout early childhood is typically due to errors of refraction. Objective: To compare refractive status in children (age 5 to 15 years) checked with subjective refraction under cycloplegia versus post mydiatric test (PMT). Methods: Comparative cross-sectional study was conducted in pediatric ophthalmic clinic of College of ophthalmology and Allied vision sciences /Mayo hospital Lahore including 120 non-pathological eyes of 60 subjects. Individuals with nystagmus and deviation of eyes were excluded. Power of SE (P1) was taken as proposed number of glasses to be dispensed. After three days PMT was done and prescription of glasses with BCVA (P2) was noted and prescribed. At PMT (P2-P1) was noted and evaluated. All data entered and analyzed by using SPSS-23. P-value equal or less than 0.05 was taken as significant. Results: Among 120 eyes (n=120), the distribution of myopia was 57.5% and hyperopia was 42%. The mean age of 60 individuals (female: 35% and male: 65%) was 9.47 ± 2.50 years. Among 120 eyes (n=120), the distribution of myopia was 57.5% (n = 69 eyes) and hyperopia was 42% (n = 51 eyes). Interclass correlation: Two-way mixed effects model where people effects are random and measures effects are fixed. a. The estimator is the same, whether the interaction effect is present or not. b. Type C intraclass correlation coefficients using a consistency definition. The between-measure variance is excluded from the denominator variance. c. This estimate is computed assuming the interaction effect is absent, because it is not estimable otherwise.